EFEK MODERASI NEED FOR ACHIEVEMENT PADA PENGARUH KOMPETENSI TERHADAP KINERJA PENGAWAS TK/SD - Sudarmanto, Untung Sriwidodo & (Universitas Slamet Riyadi, 2010)
ABSTRACT These results indicate that (1) Competency had a positive and significant on the performance of supervisors. This is indicated by the significance test of regression coefficient of competence (Î²1) with p value <0,05. (2) Need for achievement had a positive and significant on the performance of supervisors. This is indicated by the significance test of regression coefficient oh need for achievement with p value < 0,05. (3) Need for achievement does moderate on the influence of competence toward supervisor performance. This is indicated by the significance test of regression coefficient interaction (Î²3) with p value < 0,05. To improve the performance of supervisors in Education Department of Sukoharjo Regency, the competence and the need for achievement should be further improved. Need for achievement in this study had moderate effects on the performance of supervisory compe-tence, to improve the performance of the kindergarten/ elementary school supervisor in Education Department of Sukoharjo Regency, then the supervisor should always eager to improve his performance. Keywords: competence, need for achievement, supervisor performance.